2019
DOI: 10.3389/fcimb.2019.00006
|View full text |Cite
|
Sign up to set email alerts
|

Two Strains of Lactobacilli Effectively Decrease the Colonization of VRE in a Mouse Model

Abstract: Vancomycin-resistant Enterococcus (VRE) infection is a serious challenge for clinical management and there is no effective treatment at present. Fecal microbiota transplantation (FMT) and probiotic intervention have been shown to be promising approaches for reducing the colonization of certain pathogenic bacteria in the gastrointestinal tract, however, no such studies have been done on VRE. In this study, we evaluated the effect of FMT and two Lactobacillus strains (Y74 and HT121) on the colonization of VRE in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…The r-values are denoted with graduated colors, and red and blue grids indicate positive and negative correlations, respectively. "ns" indicates nonsignificance; * P < 0.05, * * P < 0.01, * * * P < 0.001. not increase the abundance of Lactobacilli and Bifidobacterium (Supplementary Figure S2) in feces and similar result was observed in our previous study (Li et al, 2019). Intake of probiotics mixture may have an effect on gut microbiota and bile acids by their metabolites as transient stay of them in intestine, which would be confirmed in the future study.…”
Section: Discussionsupporting
confidence: 90%
“…The r-values are denoted with graduated colors, and red and blue grids indicate positive and negative correlations, respectively. "ns" indicates nonsignificance; * P < 0.05, * * P < 0.01, * * * P < 0.001. not increase the abundance of Lactobacilli and Bifidobacterium (Supplementary Figure S2) in feces and similar result was observed in our previous study (Li et al, 2019). Intake of probiotics mixture may have an effect on gut microbiota and bile acids by their metabolites as transient stay of them in intestine, which would be confirmed in the future study.…”
Section: Discussionsupporting
confidence: 90%
“…It is also possible that the BTs modified the nasal microbiota in a way that conferred increased colonization resistance to M. haemolytica. A previous study showed that microbiota manipulation using probiotic Lactobacillus strains reduced the colonization of vancomycin-resistant Enterococcus (VRE) in challenged mice (26). The authors proposed that the compositional alteration observed from phylum to species level by probiotic strains may have contributed to decreased VRE colonization.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal microbiota transplantation (FMT) to decolonize VRE can also be regarded as a multiple-species treatment that reduced the colonization of VRE in a mouse model and a clinical trial [55,56]. However, FMT treatment is more invasive and it carries a risk of multiple-drug-resistant pathogenic infections.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy of administering multiple probiotic species, including L. rhamnosus and L. acidophilus , was adopted in another trial; however, it failed to prevent the colonization of ampicillin-resistant E. faecium [ 54 ], which suggested that MNA-assisted, in vitro study-supported selection of a mixture of multiple probiotics can be more promising in clinical trials. Fecal microbiota transplantation (FMT) to decolonize VRE can also be regarded as a multiple-species treatment that reduced the colonization of VRE in a mouse model and a clinical trial [ 55 , 56 ]. However, FMT treatment is more invasive and it carries a risk of multiple-drug-resistant pathogenic infections.…”
Section: Discussionmentioning
confidence: 99%